Crescimento e produção da Araucaria angustifolia (Bertol.) Kuntze em reflorestamento - Mendes, Junior Oliveira (2020)
The general objective of this thesis was to determine the growth and production of the species Araucaria angustifolia (Bertol.) Kuntze in areas of reforestation conducted in southern Brazil. The areas chosen include regions of natural growth of the species, with soil differentiation. The settlements in the state of Rio Grande do Sul are located in the municipalities of: Canela (FLONA de Canela. Mato Castelhano (FLONA of Passo Fundo), São Francisco de Paula (FLONA of São Francisco de Paula) and in the state of Santa Catarina: Caçador (FLONA of Caçador) and Guatambú and Chapecó (FLONA of Chapecó). These National Forests had their Management Plans prepared by the Department of Forest Sciences of the Federal University of Santa Maria, generating a large database of trunk analysis, cubing, temporary and permanent plots, which were used in this work. Chapter I presents the theoretical reference of the studied conservation units, as well as the creation history of each one of them; Chapter II presents a proposal of a mixed model for the prognosis of height according to diameter at breast height (dap) in the Passo Fundo National Forest, in order to obtain the reduction of the number of trees to be measured. The calibration with the five thickest trees of each sample unit was the strategy that presented the smallest standard error of the estimate, equal to 0.79 m. In chapter III the growth in diameter, height and volume of araucaria in the five conservation units was studied. The modeling was composed by linear and non-linear models and that for the first case were adjusted with dummy and mixed variables for the second case. For the three dependent variables studied, the Chapman-Richards model with random effects on parameters A and k was the one that presented the best estimates, with low error and high determination coefficient. In chapter IV an alternative is presented for the management of araucaria planted forests in southern Brazil, through Density Management Diagrams (DMD's). Data from plots were used to forecast the growth of stands in the National Forests of Rio Grande do Sul and correlate them with the number of trees per hectare and the dominant height. The management diagrams elaborated include the Relative Spacing Index, to verify the degree of competition of the stand and the Slenderness Index, to verify the degree of stability. It is possible to simulate different management strategies with good precision and low estimation error, which makes it possible to implement them for future Management Plans of the areas planted with araucaria.